The fission yeast MTREC complex targets CUTs and unspliced pre-mRNAs to the nuclear exosome - Zhou, Yang; Zhu, Jianguo; Schermann, Géza; Ohle, Corina; Bendrin, Katja; Fischer, Tamás (Nature Communications, 2015)
Cryptic unstable transcripts (CUTs) are rapidly degraded by the nuclear exosome. However, the mechanism by which they are recognized and targeted to the exosome is not fully understood. Here we report that the MTREC complex, which has recently been shown to promote degradation of meiotic mRNAs and regulatory ncRNAs, is also the major nuclear exosome targeting complex for CUTs and unspliced pre-mRNAs in Schizosaccharomyces pombe. The MTREC complex specifically binds to CUTs, meiotic mRNAs and unspliced pre-mRNA transcripts and targets these RNAs for degradation by the nuclear exosome, while the TRAMP complex has only a minor role in this process. The MTREC complex physically interacts with the nuclear exosome and with various RNA-binding and RNA-processing complexes, coupling RNA processing to the RNA degradation machinery. Our study reveals the central role of the evolutionarily conserved MTREC complex in RNA quality control, and in the recognition and elimination of CUTs.